Una necesidad curricular ante los procesos homogeneizantes de la educación contemporánea - Jiménez Corrales, Rafael (2007)
This article is an attempt to analyze the creation of new curricular proposals as a product of the convergence of institutional and personal micro processes as well as social macro processes, which are know in sociological theory as synthetic developments. This article starts on the idea that the creation of solid curricular products departs from previous historical processes, wich are then systematized and interpreted by the social actors involved, usually since opposite academic sceneries. In order to illustrate these processes, the author makes use of the construction of the Master’s Degree Program in Pedagogy of Diversity in Educational Processes Basic Education Division of the Investigation and Teaching Center of Education in the National University of Costa Rica. emphasizing the impact that social changes have on academic discussions as well as its influence on the curricular design and career development.